2017
DOI: 10.1016/j.neurobiolaging.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

CSF neurofilament light levels predict hippocampal atrophy in cognitively healthy older adults

Abstract: Cerebrospinal fluid (CSF) neurofilament light (NFL) is a marker of axonal degeneration. We tested whether CSF NFL levels predict hippocampal atrophy rate in cognitively healthy older adults independently of the established CSF Alzheimer's disease (AD) biomarkers, β-amyloid 1-42, and phosphorylated tau (P-tau). We included 144 participants in a 2-year longitudinal study with baseline CSF measures and 2 magnetic resonance images. Eighty-eight participants had full data available. A subgroup of 36 participants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 365 publications
(562 reference statements)
4
50
1
Order By: Relevance
“…In agreement with our findings, previous studies suggested that age was correlated with NFL levels in CSF [4,7,14], which were closely related with NFL levels in blood [3]. However, the mechanisms underlying this age-NFL association were largely unknown.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with our findings, previous studies suggested that age was correlated with NFL levels in CSF [4,7,14], which were closely related with NFL levels in blood [3]. However, the mechanisms underlying this age-NFL association were largely unknown.…”
Section: Discussionsupporting
confidence: 91%
“…This highlights the importance of using matched controls also in delirium research. Comorbidities, such as dementia [48], and greater age [36, 49] in an overall frailer hip fracture population are associated with increased levels of NFL in blood and CSF, as confirmed by us. A stronger correlation between NFL in CSF and blood in the elective patients compared to the hip fracture patients further suggests that extracerebral sources of NFL are of greater importance in measured sNFL in the hip fracture population.…”
Section: Discussionsupporting
confidence: 65%
“…A total of 172 patients undergoing elective gynecological, orthopedic, or urological surgery in spinal anesthesia, aged 65 years or older in the year of inclusion, were recruited to the COGNORM study from 2012 to 2013 at Oslo University Hospital and Diakonhjemmet Hospital, Oslo, as previously described [36]. Participants were evaluated with a multidomain battery of cognitive tests prior to surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Neurofilament light (NfL) is an intermediate filament protein that is expressed in neurons and believed to function primarily to provide structural support for the axon. 43 NfL is a general marker of neuronal injury and neurodegeneration and has also been detected in CSF and blood in multiple conditions including stroke, traumatic brain injury, multiple sclerosis, progressive supranuclear palsy, and frontotemporal dementia. In AD, serum NfL has been shown to be increased in AD and MCI patients compared with controls, with the highest serum levels in cases with positive amyloid PET scans.…”
Section: Neurofilament Lightmentioning
confidence: 99%